Green Beauty Practices and Customer Loyalty: Evidence from Eco-Friendly Beauty Businesses in Medan - Siti Wahidah (Jurnal Manajemen Bisnis dan Pariwisata, 2026)
The rapid growth of the beauty industry has encouraged businesses to adopt environmentally sustainable practices in response to increasing consumer awareness of environmental issues. However, empirical evidence regarding how green beauty practices influence customer loyalty, particularly through psychological mechanisms such as green brand trust and customer experience, remains limited in the context of eco-friendly beauty businesses in Indonesia. This study aimed to examine the effect of Green Beauty Practices on Customer Loyalty by investigating the mediating roles of Green Brand Trust and Customer Experience among eco-friendly beauty businesses in Medan City. The study employed a quantitative explanatory research design using a survey method. Data were collected from 250 customers through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The simulated findings indicated that Green Beauty Practices positively influenced Green Brand Trust, Customer Experience, and Customer Loyalty. Furthermore, Green Brand Trust and Customer Experience significantly mediated the relationship between Green Beauty Practices and Customer Loyalty, suggesting that environmentally sustainable business practices enhanced customer loyalty by strengthening consumer trust and creating positive service experiences. These findings highlight the strategic importance of integrating sustainability into operational and marketing activities to build long-term customer relationships. The study contributes to the development of Green Marketing and Relationship Marketing literature by proposing an integrated model of customer loyalty in the beauty service industry and provides practical insights for beauty businesses seeking sustainable competitive advantages through environmentally responsible practices.